The Influence Of Financial Literacy And Capital Market Training On Investment Decision Making At PT. Fuse Teknologi Indonesia - Ananda Hadistia; Ardi Bachtiar; Indri Kharisma (SEAN Institute, 2024)
The purpose of this study is to determine the impact of financial literacy and market knowledge on the decision to invest in PT. Fuse Teknologi Indonesia. The method used in this research is a quantitative method. The sampling technique used is called